Pengaruh Latihan Pyometric dan Resistance terhadap Peningkatan Kecepatan dan Daya Ledak Otot Tungkai - Nune Wire Panji Sakti; Johan Irmansyah (Jurnal Ilmiah Mandala Education (JIME), 2016)
Exercise physical condition, especially the speed and explosive power leg muscle needed by athletes. So that the physical conditions in all sports especially football sports need to be trained with a good workout. Exercises intended to improve the speed and explosive power leg muscle is phyomeric and resistance exercises. The purpose of this study was to assess: (1) the effect of plyometric exercises to increase speed and explosive power leg muscle; (2) the effect of resistance training to increase the speed and explosive power leg muscle; and (3) the effects of plyometric and resistance training to increase the speed and explosive power leg muscle. This type of research used in this research is quantitative with a quasi-experimental methods. The design of this research use only matching design and data analysis using ANOVA. The process of data collection is done with a test run of 30 meters and leg muscle explosive power test using a jump off during the pretest and posttest. Furthermore, the data of the present study analysis using SPSS 20.0 series. The results showed: (1) There is significant influence plyometric training program to increase speed and explosive power leg muscle; (2) There is a significant effect of resistance training program to increase speed and explosive power leg muscle; (3) There is significant differences between the effects of plyometric training program and the resistance to increasing the speed and explosive power leg muscle. Based on the above analysis, it can be concluded that there is an increase in the speed and explosive power leg muscle for each experimental group and control group after being given plyometric training and resistance seen from the results of t-test. other than that there are differences in the effect through ANOVA test, as well as plyometric exercise program is more effective than resistance training and the control group in improving the speed and explosive power leg muscle